2017
DOI: 10.3233/jad-170186
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Amyloid-β 42, Total Tau and Phosphorylated Tau are Low in Patients with Normal Pressure Hydrocephalus: Analogies and Differences with Alzheimer’s Disease

Abstract: Co-existence of Alzheimer's disease (AD) in normal pressure hydrocephalus (NPH) is a frequent finding, thus a common pathophysiological basis between AD and NPH has been postulated. We measured CSF amyloid-β 42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) concentrations in a sample of 294 patients with different types of dementia and 32 subjects without dementia. We then compared scores on neuropsychological tests of NPH patients with pathological and normal CSF Aβ42 values. Aβ42 levels were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 99 publications
7
21
1
Order By: Relevance
“…This study revealed similar neuroinflammatory histopathological changes with mild to sparse deposits of tau-immunoreactive neurofibrillary tangles in 4/5 persons with NS and 2/4 persons with another form of OAE, suggesting that NS and other forms of OAE are caused by a similar phenomenon [38]. The tau deposits most likely are induced by repetitive seizures [39] with seizure-associated hypoxia [40] and possibly repeated head injuries [41]. The decreasing incidence of both NS and OFE after strengthening onchocerciasis elimination measures suggests that both conditions may be O. volvulus-related.…”
Section: Discussionsupporting
confidence: 56%
“…This study revealed similar neuroinflammatory histopathological changes with mild to sparse deposits of tau-immunoreactive neurofibrillary tangles in 4/5 persons with NS and 2/4 persons with another form of OAE, suggesting that NS and other forms of OAE are caused by a similar phenomenon [38]. The tau deposits most likely are induced by repetitive seizures [39] with seizure-associated hypoxia [40] and possibly repeated head injuries [41]. The decreasing incidence of both NS and OFE after strengthening onchocerciasis elimination measures suggests that both conditions may be O. volvulus-related.…”
Section: Discussionsupporting
confidence: 56%
“…There have been inconsistencies in the reported levels of Aβ42 in iNPH and AD patients, with some reports of overlapping levels720 but others of lower Aβ42 levels in AD than iNPH patients 5810. These discrepancies might be due to the inclusion of different numbers of patients in the iNPH groups, possibly with coexisting AD and iNPH, since no amyloid PET analyses were performed in these previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…There is increasing evidence that soluble oligomeric assemblies of Aβ can induce neurotoxicity and synaptotoxicity in AD pathology [ 15 ], whereas mature plaques composed of insoluble fibrils are not always consistent with neuronal degeneration [ 8, 40 ]. In a review of conformation-specific antibodies targeting Aβ oligomers, Murakami also posited that Aβ oligomers can exist in a toxic form (such as Aβ-derived diffusible ligands and amylospheroid), and in a non-toxic form (such as amyloid fibrils, which comprise senile plaques).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the coexistence of an Alzheimer’s disease (AD) pathology in patients with iNPH [ 4–6 ], suggesting that AD leads to poor shunt responses [ 4, 7 ]. It is well established that Aβ 42 CSF concentrations are reduced in patients with iNPH, as seen in AD, while pTau levels in patients with iNPH are within the range of normal controls or even lower [ 8–10 ]. The similar value of Aβ 42 in AD and iNPH often presents a dilemma for clinicians in the differential diagnosis of these two diseases and in detection of AD pathology coexistence in iNPH [ 6, 10, 11 ].…”
Section: Introductionmentioning
confidence: 99%